TEST OF DIFFERENCES IN THE ABILITY OF ISLAMIC BANKS IN INDONESIA TROUGH EQUITY MANAGEMENT TO EARN PROFIT - Fauziyah, Fauziyah; Afkar, Taudlikhul (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Knowing the differences in the ability of Islamic banks in Indonesia in managing equity to earn profit is the goal in this research. Quantitative approach to this research with a population of 14 Islamic commercial banks as well as the research sample. The sampling technique used a saturated sample by using all members of the population as the research sample. The data used for comparison is before and during the COVID-19 pandemic in 2018-2021 in a time series. The findings of this study indicate that there is an increase in the ability of Islamic banks to manage their equity to earn a profit, but the increase is not statistically significant so that it can be said that there is no difference in the level of profitability before and during the COVID-19 pandemic. it means that Islamic banks have the potential to increase profitability when there is a financial recession as in the current state of the covid-19 pandemic.